সরল করি: \(\cfrac{x+\sqrt{x^2-1}}{x-\sqrt{x^2-1}}+\cfrac{x-\sqrt{x^2-1}}{x+\sqrt{x^2-1}}\) সরলফল 14 হলে, \(x\) এর মান কী কী হবে হিসাব করে লিখি ।
\(\cfrac{x+\sqrt{x^2-1}}{x-\sqrt{x^2-1}}+\cfrac{x-\sqrt{x^2-1}}{x+\sqrt{x^2-1}}\)
\(=\cfrac{(x+\sqrt{x^2-1})^2+(x-\sqrt{x^2-1})^2}{(x-\sqrt{x^2-1})(x+\sqrt{x^2-1}) }\)
\(=\cfrac{2[(x)^2+(\sqrt{x^2-1})^2 ] }{(x)^2-(\sqrt{x^2-1})^2}\)
\(=\cfrac{2[x^2+x^2-1]}{x^2-(x^2-1)}\)
\(=\cfrac{2[2x^2-1]}{x^2-x^2+1}\)
\(=4x^2-2\)
\(\cfrac{x+\sqrt{x^2-1}}{x-\sqrt{x^2-1}}+\cfrac{x-\sqrt{x^2-1}}{x+\sqrt{x^2-1}}\) এর সরলফল \(14\)
অর্থাৎ \(4x^2-2=14\)
বা, \(4x^2=14+2\)
বা, \(x^2=\cfrac{16}{4}\)
বা, \(x=\pm \sqrt{4}\)
বা, \(x=±2\)
\(∴ x\) এর মান \(±2\) হবে ।